PETROGRAFI DAN PROSES DIAGENESIS BATUGAMPING FORMASI BATURAJA DI LINTASAN AIR SAKA, OKU SELATAN, SUMATERA SELATAN - sigit Maryanto (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The Early Miocene limestone  of  Baturaja Formation crops out along the Air Saka Section, having a measured  thickness  of 247 metres. This carbonate  formation  lies conformabty  on the siliciclastic  sediments  of Talangakar Formation, and it is in turn, conformably   overlain  by the silicidastic  sediments   of Gumai  Formation.  The limestone was affected  by several diagenetic processes, such as bioturbation,   fossil cavity filling,  replacement,  cementation, recrystallization, micritization, dolomitization,  authigenic-mineral  formation, compaction,   dissofution,   stylolitization, and fracturing.  Some  of these diagenetic processes have a very weak to moderate coeficient  of interrelationship. Keywords:Petrography, carbonate grains, cementation, meteoric, statistical test